Person-portable equipment in environmental forensic investigations: application to fire scenes. Issue 6 (2nd November 2018) - Lam, Rylee; Lennard, Chris; Kingsland, Graham; Johnstone, Paul; Symons, Andrew; Wythes, Laura; Fewtrell, Jeremy; O'Brien, David; Spikmans, Val
Abstract: Environmental forensic investigations can be complex because pollutants are often not visible, making it difficult to determine the types of pollutants and their source. Emergency scenarios require immediate action to protect environmental and/or human health, and having limited knowledge of these pollutants makes this complicated. Recent advancements in field-portable instrumentation pave the way for rapid on-site analyses for real-time monitoring of hazardous compounds at incident sites, thereby providing valuable intelligence to direct subsequent actions. Fires can pose significant risk to human and/or environmental health through the release of hazardous compounds in smoke or run-off water from firefighting activities. Monitoring the release of hazardous organic compounds from fires typically requires complex sampling and laboratory-based protocols. Results from such protocols are not immediately available to first responders. Site risk assessment and management would therefore benefit from accurate in-field identification of the release of hazardous organic compounds. A portable Gas Chromatograph – Mass Spectrometer (GC-MS) was evaluated for the identification of hazardous organic compounds in air and water samples at fire scenes. Preliminary results demonstrated that deployment of such instrumentation has the potential to provide first responders with a rapid on-site assessment tool, allowing for more proactive protection of environmental and human health.